2018
DOI: 10.1029/2018gl079511
|View full text |Cite
|
Sign up to set email alerts
|

Slower Snowmelt in Spring Along With Climate Warming Across the Northern Hemisphere

Abstract: Climate warming is altering historical patterns of snow accumulation and ablation, hence threatening natural water resources. We evaluated the impact of climate warming on snowmelt rates using the GlobSnow v2.0 and the second Modern‐Era Retrospective analysis for Research and Applications data sets over the Northern Hemisphere (NH) during the past 38 years (1980–2017). Higher ablation rates were found in the locations with deeper snow water equivalent (SWE) because high snow melt rates occurred in late spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 40 publications
7
22
0
Order By: Relevance
“…Furthermore, a strange phenomenon that the variation trend of seasonal maximum SD in the Russian Far East show extremely significant decrease, while it is in inverse in spring. This variation trend of maximum SD in spring analyzed using NHSnow products is consistent with the analysis results using GlobSnow products from recently published study (Wu et al, 2018). It need be pointed out that the significant increase (decrease) area is located around extremely significant increase (decrease) as shown in Figure 8.…”
Section: Variation Of Snow Depthsupporting
confidence: 90%
“…Furthermore, a strange phenomenon that the variation trend of seasonal maximum SD in the Russian Far East show extremely significant decrease, while it is in inverse in spring. This variation trend of maximum SD in spring analyzed using NHSnow products is consistent with the analysis results using GlobSnow products from recently published study (Wu et al, 2018). It need be pointed out that the significant increase (decrease) area is located around extremely significant increase (decrease) as shown in Figure 8.…”
Section: Variation Of Snow Depthsupporting
confidence: 90%
“…The seasonal maximum SD variations in fall and winter in Russian Far East exhibit the extremely significant decrease trend, while in spring, it shows an extremely significant increase trend. This variation trend of maximum SD in spring, analyzed using NHSnow products, is consistent with the analysis results obtained using GlobSnow products (Wu et al, 2018),…”
supporting
confidence: 89%
“…The primary reason for the increase of SD may be due to the increase in the frequency of extreme snowfall. Additionally, a recent study found that the greater SWE, the faster melting rate leading to a shortened SCD in the Northern Hemisphere (Wu et al, 2018).…”
mentioning
confidence: 98%
“…In many regions, especially in cold mountainous watersheds (Dozier et al, 2016;Li & Williams, 2008;Yin et al, 2016), snowmelt runoff supplies the majority of water resources in the middle and lower reaches of these systems. Under rapid climate change, hydrological processes, including snowmelt processes, have been greatly affected (Pachauri et al, 2014;Wu et al, 2018). A series of hydrological responses to temperature and precipitation change, including time shifts and volume changes in springtime snowmelt discharge, have been observed over the past few years in many regions, including North America (Stewart et al, 2004(Stewart et al, , 2009Tang et al, 2019), the Tibetan Plateau (Immerzeel et al, 2010), Europe (Kay, 2016), and central Asia (Yucel et al, 2015); thus, the accurate evaluation of snowmelt contributions will be increasingly important in the future.…”
Section: Introductionmentioning
confidence: 99%